DEFINING THE CONCEPT OF ARTS AND CULTURE IN HIGHER EDUCATION SYSTEMS IN INDONESIA - Pham Tran Minh Thi (FBS UNY, 2020)
An understanding of art and culture has often been known by many Indonesian students and also the community. These two words are always a pair of words in the vocabulary of the Language and Arts department in particular. there is art where the culture is, and vice versa culture is never released by the art. However, the definitions of